2010
DOI: 10.1007/s11259-010-9377-2
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin activity in spontaneously hypertensive rats (SHR): preliminary studies in vivo

Abstract: An elevation in angiotensin II (Ang II) levels is a common occurrence in spontaneously hypertensive rats (SHRs). Infusions of Ang II and a high salt diet increase the activity of NADPH oxidase that stimulates superoxide anion (O −2 ) generation and increases the expression of certain subunits of NADPH oxidase. Apocynin, an NADPH oxidase inhibitor with antihypertensive effects, is able to inhibit the release of superoxide anion by inhibiting NADPH oxidase activity and blocking the migration of p47 phox to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Subsequently, H 2 O 2 significantly increased the cell apoptosis rate ( Figures 3A, B). Previous studies showed that ROS directly reflects the level of oxidative stress in cells (Ciarcia et al, 2010). Our experiment also indicated that the intracellular ROS level is consistent with cell damage, with a significant decrease in cell viability after the ROS level is increased.…”
Section: Discussionsupporting
confidence: 84%
“…Subsequently, H 2 O 2 significantly increased the cell apoptosis rate ( Figures 3A, B). Previous studies showed that ROS directly reflects the level of oxidative stress in cells (Ciarcia et al, 2010). Our experiment also indicated that the intracellular ROS level is consistent with cell damage, with a significant decrease in cell viability after the ROS level is increased.…”
Section: Discussionsupporting
confidence: 84%
“…Different studies have been using apocynin [32,[60][61][62][63][64] and diapocynin [25,27,28] for treatment of experimental animal models to evaluate the role of NAD(P)H oxidase enzyme and the contribution of ROS to oxidative stress and cardiovascular disease. Then, the intent of our study was elucidating the clinical pharmacology of diapocynin on vascular system and its vasodilator and hypotensive effect, once is an active dimer from apocynin and thus our data could contribute to the progress of the field for ROS study and vascular biology.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is further supported by findings that in isolated arteries presence of ADMA increased ethidium bromide fluorescence, an indicator of vascular oxidative stress, which was reduced by apocynin [18]. The primary cellular effect of apocynin is to inhibit the release of superoxide anion by inhibiting NADPH oxidase activity via blocking the migration of p47 phox to the plasma or microsomal membranes [50]. …”
Section: Discussionmentioning
confidence: 73%